2015
DOI: 10.18632/oncotarget.4292
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-153/Nrf-2/GPx1 pathway regulates radiosensitivity and stemness of glioma stem cells via reactive oxygen species

Abstract: Glioma stem cells (GSCs) exhibit stem cell properties and high resistance to radiotherapy. The main aim of our study was to determine the roles of ROS in radioresistance and stemness of GSCs. We found that microRNA (miR)-153 was down-regulated and its target gene nuclear factor-erythroid 2-related factor-2 (Nrf-2) was up-regulated in GSCs compared with that of non-GSCs glioma cells. The enhanced Nrf-2 expression increased glutathione peroxidase 1 (GPx1) transcription and decreased ROS level leading to radiores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 51 publications
2
61
0
1
Order By: Relevance
“…In order to identify whether miR-146b-5p targets HuR by binding to its 3′ UTR sequence (Figure 4B), we employed luciferase reporter assays. Generally, a declined luminescence indicated that the 3′-UTR was effectively bound and targeted by the miRNA [33, 34]. As shown in Figure 4C, after miR-146b-5p oligos were transfected into GSCs with the wild type reporter construct pGL3-Luc-HuR, luciferase activity was significantly decreased compared with scramble oligos transfection, whereas mutations in predicted target site of 3′-UTR of HuR gene abrogated the inhibition by miR-146b-5p oligos.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to identify whether miR-146b-5p targets HuR by binding to its 3′ UTR sequence (Figure 4B), we employed luciferase reporter assays. Generally, a declined luminescence indicated that the 3′-UTR was effectively bound and targeted by the miRNA [33, 34]. As shown in Figure 4C, after miR-146b-5p oligos were transfected into GSCs with the wild type reporter construct pGL3-Luc-HuR, luciferase activity was significantly decreased compared with scramble oligos transfection, whereas mutations in predicted target site of 3′-UTR of HuR gene abrogated the inhibition by miR-146b-5p oligos.…”
Section: Resultsmentioning
confidence: 99%
“…The human glioma cell lines U87 were purchased from the Type Culture Collection of the Chinese Academy of Sciences and cultured in DMEM/F12 medium (1:1, Hyclone) supplemented with 10% fetal bovine serum (FBS) (Invitrogen) in a humidified atmosphere containing 5% CO2 at 37°C. The human GSCs culture U87s, derived from glioma cell line U87, were enriched using serum-free clone formation method with stem cell medium, which has been previously described [33]. The patient-derived GSCs culture SU-2 and non-GSCs glioma cell culture NSSU-2, isolated from a surgical specimen of a 52-year-old female patient with glioblastoma, were kindly provided by Dr. Ting Sun in neurosurgery laboratory of the first affiliated hospital of Soochow University [33, 47, 48].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations